Ideological Tendencies in the Six English Qur’an Translation on Qs. Ar-Rum 41 - Afif Suaidi; Moh Nur Arifin (UIN Sunan Kalijaga Yogyakarta, 2021)
Lessons from the Qur’an can be learned from its translation by those who do not understand Arabic, although the Qur’an does not state the meaning obviously. Still, some translators may interpret the Qur’an differently from each other depend on what ideology belongs to the translators. To know the ideology, this study employs Systemic Functional Linguistic (SFL) approach. The sources of data of this research are six English Qur’an translational texts. The research data are clause unites in the English Qur’an translation of the QS. Ar-Rum 41. They are divided into four clauses. The results showed that the translation of the Qur’an has a connection with the ideology embraced by translators. Saheeh International – Jeddah Qur’an translation bears the Aswaja ideology consistenly; Maulawi Sher Ali – Islamabad Qur’an translation bears the Ahmadiyah ideology consistenly; Dr. Muhammad Taqi-ud-DIn Al-Hilali, and Dr. Muhammad Muhsin Khan - Madinah Al-Munawwarah Qur’an translation bears the Sunni ideology consistenly. Edip Yuksel – US Qur’an translation bears the ideology of reformism combined with the ideology of Ahlussunnah, Ahmed Ali Qur’an translation bears the ideology of reformism combined with the ideology of tafsiriyah that makes it less stylish, and Aisha Bewley Qur’an translation bears the ideology of Liberal and stylistic. The variety of ideologies in the English Qur’an translation is due to the influence of religious understanding of the authors as well as their efforts to promote specific ideologies in the English Qur’an translation.